Experimental study of mechanical and fresh properties of HVFA-SCC with and without PP fibers. (18th January 2021) - Zhou, Lingzhu; Zheng, Yu; Yu, Yong; Song, Gangbing; Huo, Linsheng; Guo, Yongchang
Graphical abstract: Highlights: The fresh and mechanical properties of HVFA-SCCs are revealed. The mix proportion design scheme of HVFA-SCC with 0.5% PP fibers is proposed. The using of seawater and sea-sand can improve the crack resistance of HVFA-SCCs. SCC with fly ash of 50% is feasible for large-scale constructions. Seawater and sea-sand HVFA-SCCs can be potentially used in coastal engineering. Abstract: This paper aims to study the mechanical and fresh properties of novel high-volume fly ash-self compacting concretes (HVFA-SCCs). Firstly, the mechanical and flowability properties of SCCs with different fly ash replacement ratio are investigated. Thereafter, the high-volume polypropylene (PP) fibers were added into the HVFA-SCC, and the effects of some parameters on its performance are explored for proposing its mix proportion design scheme. Finally, the hardening and fresh properties of seawater and sea-sand HVFA-SCCs are discussed. The results show that HVFA-SCC, high-volume PP fibers reinforced HVFA-SCC, seawater and sea-sand HVFA-SCC are feasible used in various constructions.